Cancer risk among 21st century blood transfusion recipients - Yang, T; Cairns, B; Reeves, G; Green, J; Beral, V (Oxford University Press, 2016)
Background: Some viruses are known to be transmissible by blood transfusion. Intensive viral screening of transfused blood now exists in most countries. In the UK, high-sensitivity nucleic acid amplification tests for hepatitis C virus were introduced in 1999 and it was thought that this would reduce, and possibly eliminate, transfusion-related liver cancer. We aimed to investigate cancer risk in recipient of blood transfusion in 2000 or after. Methods: 1.3 million UK women recruited in 1998, on average, were followed for hospital records of blood transfusion and for cancer registrations. After excluding women with cancer or precancerous conditions before or at the time of transfusion, Cox regression yielded adjusted relative risks of 11 site-specific cancers for women with compared to without prior blood transfusion. Results: During follow up, 11,274 (0.9%) women had a first recorded transfusion in 2000 or after, and 1648 (14.6%) of them were subsequently diagnosed with cancer, a mean 6.8 years after the transfusion. In the first 5 years after transfusion there were, as expected, significant excesses for most site-specific cancers examined, presumably because some had preclinical cancer. However, 5 or more years (mean 8 years) after blood transfusion there were significant excess risks only for liver cancer (relative risk=2.63, 95%CI 1.45-4.78) and for non-Hodgkin lymphoma (relative risk=1.74, 1.21-2.51). When analyses were restricted to those undergoing hip or knee replacement surgery, the commonest procedure associated with transfusion, these risks were not materially altered. Conclusions: In a large cohort of UK women, 21st century transfusions were associated with long-term increased risks of liver cancer and non-Hodgkin lymphoma. These findings suggest that some cases of liver cancer and non-Hodgkin lymphoma are caused by carcinogenic agents that are not currently screened for in transfused blood.